Educational strategies for future engineers: understanding nano-adsorbents in carbon capture and storage technologies - Santi Febri Arianti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Climate change and increasing carbon dioxide (CO₂) emissions demand technological innovations that can support effective climate change mitigation. One of the rapidly growing solutions is the use of nano-adsorbents in carbon capture and storage (CCS) technology, which is able to improve CO₂ absorption efficiency through high surface area and adjustable porosity. However, although the effectiveness of this technology has been proven in various studies, its integration in engineering education is still limited, so aspiring engineers lack sufficient understanding and skills in implementing this solution in the industrial world. This research aims to develop a systematic educational strategy to integrate nano-adsorbent learning in the engineering curriculum, by emphasizing an experiential approach and industry collaboration. The study used a blended method, which combined qualitative insights from interviews and focus groups with quantitative data from surveys of students and engineering faculty. The results showed that 68% of students did not get adequate exposure to nano-adsorbent technology, while 84% of respondents supported the addition of related materials in the engineering curriculum. In addition, only 35% of students have direct experience with this technology through labs or industrial internships, indicating the need for reform in the engineering learning system. As a contribution to the academic literature, this research provides an innovative educational model that combines nano-technology with sustainability-based engineering learning strategies. By proposing curriculum reforms, improved laboratory access, as well as partnerships with the CCS industry, the research not only provides concrete solutions for academia but also contributes to strengthening the skills of future engineers in low-carbon technologies. The implementation of this model is expected to increase the readiness of engineering graduates to support the transition to a more environmentally friendly industry and accelerate climate change mitigation through more effective CCS technology.